Creation of the development strategy in enterprise based on dynamic SPACE-analysis - Valeriy Balan; Inna Tymchenko (Cхід)
Development strategy of using modern portfolio theory focused on the short term. However, macroeconomic uncertainty and geopolitical environment makes their use ineffective. And challenge is to provide a reasonable balance between the short and long term profitability. Another issue, which is to some extent related to the previous observation is the absence in most matrices strategic recommendations for non-standard "behavior" of business units with dynamic analysis. This applies to the use of a relatively new tool matrix approach to development strategies the company and its strategic business units - SPACE-analysis that also takes into account not forecasts of changes in the environment impact on the company.